A new estimator and its performance / Ng Set Foong, Low Heng Chin and Quah Soon Hoe - Ng, Set Foong; Low, Heng Chin; Quah, Soon Hoe (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2009)
The Ordinary Least Squares Estimator is an unbiased estimator in estimating parameters in a linear regression model. In this paper, a new estimator is proposed as an alternative of the Ordinary Least Squares Estimator for linear regression model. The performance of this new estimator is compared with other estimators in terms of mean squared error.